Reduction of aspirin bioavailability by cimetidine - R.H.Yudono, R.H.Yudono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1984)
The effect of cimetidine on the oral bioavailability of aspirin has been investigated in seven healthy adult volunteers. The estimation of bioavailability was performed by calculating the amount of the total salicylate recovered in the 72 hour urinary sample following an oral aspirin dose of 500 mg, first during control and second after pretreatment with oral cimetidine (RlUlcedin) 400 mg single dose given one hour prior to the administration of aspirin.The bioavailability of aspirin after cimetidine (36.5% ÃÂ± SEM 4,2%) was significantly (paired. t-test, P